Evaluation of transverse maxillary expansion in adults using MARPE versus SARPE: a systematic review - Sousa Santos, Primavera (2022)
Introduction: The prevalence of maxillary atresia is high in the population. Conventional maxillary expansion is not always a good solution due to fusion of the midline suture. Objective: Compare the two maxillary expansion techniques, MARPE and SARPE, used in the treatment of transverse maxillary discrepancy, thus evaluating the skeletal and dentoalveolar changes and the influence of age on the choice of treatment. Materials and methods: A bibliographic search was performed in the PubMed database using the keywords ''Mini-implant-assisted Rapid Palatal Expansion'', ''Surgically Assisted Rapid Palatal Expansion'', “'Maxillary'', and ''Expansion''. Results: MARPE has been described in the literature as a technique of first choice in young patients and young adults with maxillary atresia, with the ability to reduce the side effects caused by the conventional appliance, such as gingival recession, excessive dental buccal tipping and bone dehiscence. SARPE is an effective treatment modality in adult patients, but it is a complex treatment as it requires hospitalization and the presence of a surgeon. Conclusion: MARPE and SARPE were considered to be effective procedures. However, MARPE is a viable alternative to SARPE, allowing minimization of biological and financial costs.